Values of Ahlussunnah wal Jama'ah in Commemorating the Gregorian New Year - Setiawan, Hendra; Aufa, Ari Abi (Letiges, 2024)
Kolong Village, Ngasem District, Bojonegoro Regency, has a unique tradition where 85 Catholics have celebrated the New Year with Muslims since 1954 while commemorating the founding of the Santa Maria Church. This tradition is the basis for the Bojonegoro Regency Religious Harmony Forum to designate Kolong Village as a Harmonious Village on August 30 2022. This research aims to describe the values ??of Ahlussunnah Wal Jama'ah in commemorating the Gregorian New Year together, using qualitative methods with a study approach case. Data analysis uses Miles and Huberman analysis techniques. Tawassuth's values ??are reflected in Banser's role in maintaining church order, creating a sense of security, and promoting tolerance between religious communities. Tasamuh's values ??show that respecting differences does not change his beliefs but supports harmony between religious communities. The value of i'tidal can be seen in the presence of Islamic figures from various organizations who stay in touch and strengthen harmony, reflecting justice and cooperation in society. The value of Tawazun can be seen when Muslims and Catholics pray according to their respective beliefs, creating a balance between practising the Shari'a and respecting religious differences as a form of resignation and gratitude for the grace of Allah SWT.